Mesenchymal Stem Cell (MSC) Secretome and Vitamin C Combination Additively Enhance Epidermal Keratinocyte Proliferation and Morphology: Evidence from Intrinsic and Extrinsic Rat Skin Aging Models - Olivia Belinda; Veronika M Sidharta; Komang A Wahyuningsih; Reynelda J Sagala; Christania Christania; Vallery B Setiawan; Nadia A Sjoekri; Renata Angelia; Laurie Marcella (Universitas Kristen Maranatha, 2026)
Skin aging, driven by intrinsic and extrinsic factors, impairs keratinocyte proliferation and morphology. Mesenchymal stem cell (MSC) secretome and vitamin C possess regenerative and anti-aging properties that may counteract these changes. This study aimed to evaluate the additive effects of MSC secretome and vitamin C on keratinocyte proliferation and morphology in intrinsic and extrinsic rat skin aging models. Thirty-two male Sprague-Dawley rats were randomly divided into eight groups: intrinsic aging control (IAC; D-galactose-induced), extrinsic aging control (EAC; UVB-induced), MSC secretome-treated (IS and ES; 0.2 mL MSC secretome), vitamin C-treated (IC and EC; 0.2 mL vitamin C at 75 μg/mL), and combination-treated (ISC and ESC; 0.1 mL of each treatment). Treatments were administered intradermally once weekly for four weeks. Histological analysis assessed keratinocyte count and size in the stratum granulosum and stratum basale. Combination treatment (ISC, ESC) produced the most pronounced and statistically significant increases in keratinocyte counts and reductions in cell size across both strata (p < 0.01 to ≤ 0.001), whereas individual treatments showed variable effects, with most failing to reach statistical significance. These findings suggest that combined MSC secretome and vitamin C treatment produces the most pronounced histological effects in keratinocyte counts and size, likely reflecting complementary actions, and supports its potential as a cell-free anti-aging therapy.